Enhancing student success through professionalised academic advising: A model for identifying academic advisors for South African higher education contexts - de Klerk, D.; Jadhav, A.; Hundermark, G. (South African Journal of Higher Education, 2024)
At South African universities, the role of academic advisors is not easily defined and there is limited literature about the attributes and characteristics required of those who occupy advising positions in the country. This article proposes a model for identifying academic advisors for South African higher education contexts. The authors adopt a phenomenological approach to construct this model. Based on existing literature and data collected from advising interactions with students, the authors share and explain their model for identifying suitable candidates for academic advisor roles in South African higher education contexts. The model consists of seven dimensions: cultural quotient, data analytics, personal/ emotional support, psychosocial and socioeconomic support, scholarly activities and networking, skills formation and support, and teaching and learning. The authors conclude by emphasising the importance of academic advising for South Africa, before making recommendations for using the model to identify suitable candidates for advisor roles.